Symmetrical Peripheral Gangrene Post Snake-Bite: An Unusual Presentation (Indian Journal of Case Reports, 2017)
Snake bite in India is a common yet neglected public health issue, with an estimated death rate of 50,000 per year. Symmetrical peripheral gangrene (SPG) has varied aetiology, but it is an unusual complication after snake bites. SPG is important as it causes significant morbidity and mortality, and early intervention may improve the outcome. Hereby, we report a case of SPG in young female with history of snake bite. The patient developed gangrene of bilateral foot and distal part of legs with necrotising fasciitis of right leg. In the literature, there are only few reported cases of SPG as a complication of snake bite.